I'm trying to solve a recurrence relation

$\displaystyle \sum_{i=0}^{n}\binom{n}{i}\frac{A_i}{(n-i+1)}=0$, where $A_0=1$

first few terms are $A_1=-\frac{1}{2}$, $A_2=\frac{1}{6}$, $A_3=0$, $A_4=-\frac{1}{30}$, $A_5=0$, $A_6=\frac{1}{42}$, $A_7=0$, $A_8=-\frac{1}{30}$ .

It seems like $A_n=0$ for odd number $n$

but I can't find pattern for even term.

Note that the relation is similar to Catalan number's recursive formula
$\displaystyle C_n =\sum_{i=0}^{n-1}\binom{2n-2k-1}{n-k-1}\frac{C_i}{n-1} $ , $C_0=1$ whose solution is $C_n = \frac{1}{n+1}\binom{2n}{n}$,

Thanks for helping.


1 Answer 1


These are the Bernoulli numbers.

See https://en.wikipedia.org/wiki/Bernoulli_number


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.